Telaah Kitab al-Minhah al-Khairiyyah Tentang Hadis Anjuran Menyayangi Terhadap Sesama Perspektif Syaikh Mahfudz al-Tarmasi - shintakristantiarasamudra; Syeha Ibrahim; Muhid; Isnaini Lu'lu' Atim Muthoharoh (Universitas Majalengka, 2024)
This research aims to examine one of the works of Shaykh Mahmfudz, namely al-Minhah al-Khairiyyah fi Arba'in Haditsan min Ahadis Khair al-Bariyah. It aims to quote the hadith of affection in the book and provide an understanding of Shaykh Mahfudz al-Tarmasi's perspective by explaining the biography and content of the book. Qualitative methods and library research are methods used by authors to obtain results and discussions. The hadith of rahma is a study of this article, whose understanding is studied through the perspective of Shaykh Mahfudz al-Tarmasi, presenting sha'ir-sha'ir by scholars and clarifying the importance of having the nature of affection. Understanding the hadith from the perspective of Shaykh Mahfudz al-Tarmasi and the hadith of encouraging love invites Muslims to have compassion for others and reduce the crisis of humanitarian concern.